Prediksi Kebutuhan Area Permukiman di Kota Ternate - Vrita Tri Aryuni; Ramdani Salam; Anif Farida (Universitas Udayana, 2021)
Abstract Ternate City is a densely populated area and has high population growth in comparison with other cities of North Maluku, Indonesia. Consequently, Ternate needs more areas dedicated for settlement than it currently has. In addressing this condition, this study aims at examining the scale of land needed to accommodate the escalating number of houses required by Ternate’s urban dwellers in 2025, 2030, and 2035. It adopts a quantitative method supported by relevant and available secondary data. The increase in population number is calculated based on an exponential growth calculation. Discussion within is developed based on an assumption that every household needs a minimum of 100 m2 for its home. This study shows that each district of Ternate has its own need for houses and scale of area that differ from one district to another. The southern part of Ternate City demonstrates the highest figure of 27.992 unit houses with an area of 279,92 hectares in 2025; 36.345 units of houses and an area of 363,45 hectares in 2030; and 4.962 units of houses with an area of 49,62 hectares in 2035. On the other side, Ternate Island shows the least figure of 3.113 units of houses with an area of 31,13 hectares in 2025; 3.928 units of houses with an area of 39,28 hectares in 2030; and 4.962 units of houses with an area of 49,62 hectares in 2035. On top of these, this study further recommends that the escalating needs for urban settlement should be well addressed in the urban plan formulated by the Local Urban Planning Office of the Ternate City, thus uncontrolled land conversion will not take place in the near future. Keywords: population, land, settlement, needs projection Abstrak Kota Ternate merupakan daerah yang padat penduduk dan memiliki pertumbuhan penduduk yang tinggi dibandingkan kota-kota lain di Maluku Utara, sehingga membutuhkan lebih banyak permukiman. Tujuan penelitian yaitu untuk memprediksi kebutuhan lahan permukiman di Kota Ternate pada tahun 2025, 2030 dan 2035. Penelitian ini menggunakan metode kuantitatif dengan data sekunder. Prediksi populasi penduduk dihitung dengan pertumbuhan eksponensial. Kebutuhan permukiman penduduk diperoleh dengan asumsi setiap rumah tangga membutuhkan luas minimal 100 m2. Hasil penelitian menunjukkan bahwa kebutuhan lahan permukiman berbeda pada tiap kecamatan. Ternate Selatan membutuhkan jumlah rumah mukim terbanyak dan lahan permukiman terluas yaitu 27.992 unit dengan luas 279,92 ha pada tahun 2025, 36.345 unit dengan luas 363,45 ha pada tahun 2030, dan 47.805 unit dengan luas 478,05 ha pada tahun 2035. Pulau Ternate yang paling sedikit membutuhkan rumah mukim dan lahan permukiman tersempit yaitu 3.113 unit dengan luas 31,13 ha pada tahun 2025, 3.928 unit dengan luas 39,28 ha pada tahun 2030 dan 4.962 unit dengan luas 49,62 ha pada tahun 2035. Meningkatnya kebutuhan akan lahan permukiman tersebut sebaiknya diiringi penataan kota oleh Pemerintah Daerah setempat, agar tidak terjadi konversi lahan yang tidak terkendali di masa depan. Kata kunci: populasi, lahan, area permukiman, prediksi kebutuhan